Migration, Fiscal Competition and Brain Drain - Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
In this paper I present a simple model in which I analyse the impact of labor mobility on redistributive policies and the provision of education as a publicly provided good. I've analysed different extensions of the model (Maximin objective function of the government and utilitarian function, symmetric and asymmetric population, one generation and two generation model) for check the results in different specifications of the world. The results obtained are in agreement to the literature: less redistribution and less provision of public good with respect to the efficient value (which could be obtained in the absence of mobility or in the presence of coordination among jurisdictions) The aim of this work is to underline this particular aspect of the fiscal competition: when we add up the two negative effects due to the absence of coordination among jurisdictions, the loss of efficiency is more accentuate. This result is important in the European contest because we have an increase of labor mobility. For this reason the possibility of brain drain added to fiscal competition and to an increase of the mobility can be more dangerous for the European jurisdictions and a coordination is necessary in the education policies and in the redistribution policies within the European Union.
Keywords: 330